The Accuracy of Social Assistance Based on DTSEN (Single Social and Economic Data) in Reducing Poverty in The City of Serang - Kristina Kuryestra Halawa; Laeli Nur Khanifah; Syaira Azzahra Putri; Rizki Saeful Bahri; Ghithrifan Dheriel Lubis (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Poverty remains a multidimensional development challenge that extends beyond income deprivation and is closely associated with unequal access to education, healthcare, employment opportunities, housing, and social protection. This study analyzes the accuracy of DTSEN-based social assistance targeting in poverty alleviation efforts in Serang City, focusing on the Family Social Security Program (Jamsos) and Productive Economic Enterprise Assistance (UEP). A qualitative case study approach was employed through interviews, observations, and document analysis involving social welfare officials, program facilitators, beneficiaries, and eligible non-beneficiaries. The findings indicate that DTSEN has strengthened beneficiary identification through a more integrated socioeconomic database. Targeting accuracy, however, remains affected by data validation challenges, inter-agency coordination issues, budget limitations, and changes in household socioeconomic conditions. Jamsos contributes to short-term social protection by reducing the burden of basic household expenditures, while UEP provides opportunities for economic empowerment despite uneven outcomes among beneficiaries. Effective poverty alleviation requires continuous data updating, stronger monitoring mechanisms, institutional coordination, and sustained capacity-building efforts to enhance long-term economic independence.